Clinical Evaluation of positioning verification using digital tomosynthesis (DTS) based on bony anatomy and soft tissues for prostate image-guided radiation therapy (IGRT) - Yoo, Sua (2009)
PURPOSE: To evaluate on-board digital tomosynthesis (DTS) for patient positioning in comparison with 2D-radiographs and 3D-CBCT. METHODS AND MATERIALS: A total of 92 image sessions from 9 prostate cancer patients were analyzed. An on-board image set was registered to a corresponding reference image set. Four pairs of image sets were used; DRR vs. on-board orthogonal paired radiograph for the 2D method, coronal-reference-DTS (RDTS) vs. on-board coronal-DTS for the coronal-DTS method, sagittal-RDTS vs. on-board sagittal-DTS for the sagittal-DTS method, and planning CT vs. CBCT for the CBCT method. Registration results were compared. RESULTS: The systematic errors in all methods were less than 1 mm/1°. When registering bony anatomy, the mean vector differences were 0.21±0.11 cm between 2D and CBCT, 0.11±0.08 cm between CBCT and coronal-DTS, and 0.14±0.07 cm between CBCT and sagittal-DTS. The correlation of CBCT to DTS was stronger (coefficients=0.92–0.95) than the correlation between 2D and CBCT or DTS (coefficients=0.81–0.83). When registering soft tissue, the mean vector differences were 0.18±0.11 cm between CBCT and coronal-DTS and 0.29±0.17 cm between CBCT and sagittal-DTS. The correlation coefficients of CBCT to sagittal-DTS and to coronal-DTS were 0.84 and 0.92, respectively. CONCLUSIONS: DTS could provide equivalent results to CBCT when bony anatomy is used as landmarks for prostate IGRT. For soft tissue-based positioning verification, coronal-DTS produced equivalent results to CBCT and sagittal-DTS alone was insufficient. DTS could allow comparable soft tissue-based target localization with faster scanning time and less imaging dose compared to CBCT.